Effect of ceramic coating thickness on fracture behaviour of coating structure under thermal shock cycles. Issue 8 (15th April 2022) - Liang, L.H.; Liu, X.H.; Chen, L.F.; Wei, Y.G.
Abstract: Ceramic coatings are commonly used to fulfil some form of protection function, such as thermal protection, electric isolation, or corrosion resistance. However, coating failure caused by mechanical mechanisms can reduce the effectiveness of these functions. In this study, the effect of the coating thickness of thermal barrier coatings on fracture behaviour was investigated to understand its importance and the related mechanical mechanisms. Thermal shock cycling experiments were conducted with a corresponding stress analysis based on the finite element method. The results indicate that coatings thicker than 300 μm are more likely to fail after a low number of cycles, the number of cycles at the failure of 500 μm coatings is only 16.6% of that of 100 μm coatings, and the underlying mechanism can be explained as the larger compressive stress influence of thicker coatings. The residual compressive stress increased to 125 MPa only after ten cycles for 300 μm coatings.